Genomic ERBB2/ERBB3 mutations promote PD-L1-mediated immune escape in gallbladder cancer: a whole-exome sequencing analysis. Issue 6 (28th June 2018) - Li, Maolan; Liu, Fatao; Zhang, Fei; Zhou, Weiping; Jiang, Xiaoqing; Yang, Yuan; Qu, Kai; Wang, Yueqi; Ma, Qiang; Wang, Ting; Bai, Lu; Wang, Zheng; et al.
Abstract : Objectives: Patients with gallbladder carcinoma (GBC) lack effective treatment methods largely due to the inadequacy of both molecular characterisation and potential therapeutic targets. We previously uncovered a spectrum of genomic alterations and identified recurrent mutations in the ErbB pathway in GBC. Here, we aimed to study recurrent mutations of genes and pathways in a larger cohort of patients with GBC and investigate the potential mechanisms and clinical significance of these mutations. Design: We performed whole-exome sequencing (WES) in 157 patients with GBC. Functional experiments were applied in GBC cell lines to explore the oncogenic roles of ERBB2 / ERBB3 hotspot mutations, their correlation with PD-L1 expression and the underlying mechanisms. ERBB inhibitors and a PD-L1 blocker were used to evaluate the anticancer activities in co-culture systems in vitro and in vivo. Results: WES identified ERBB2 and ERBB3 mutations at a frequency of 7%–8% in the expanded cohort, and patients with ERBB2 / ERBB3 mutations exhibited poorer prognoses. A set of in vitro and in vivo experiments revealed increased proliferation/migration on ERBB2 / ERBB3 mutation. Ectopic expression of ERBB2/ERBB3 mutants upregulated PD-L1 expression in GBC cells, effectively suppressed normal T-cell-mediated cytotoxicity in vitro through activation of the PI3K/Akt signalling pathway and contributed to the growth and progression of GBC in vivo. Treatment with an ERBB2/ERBB3 inhibitor or a PD-L1 monoclonal antibody reversed these immunosuppressive effects, and combined therapy revealed promising therapeutic activities. Conclusions: ERBB2 / ERBB3 mutations may serve as useful biomarkers in identifying patients who are sensitive to ERBB2/ERBB3 inhibitors and PD-L1 monoclonal antibody treatment. Trial registration number: NCT02442414 ;Pre-results.